Clinical profile of hypertensive crisis presenting as urgency and emergency in an emergency department of eastern Nepal - Kshetri, Samir; Bhandari, Rabin; Gupta, Pramendra Prasad; Yadav, Ajay; Chaudhary, Ritesh; Shrivastav, Vijay Kumar; Bhandari, Rupak (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Hypertensive crisis (HTN-C) encompasses hypertensive urgency (HTN-U) and hypertensive emergency (HTN-E), distinguished by presence or absence of acute target organ damage, respectively. Early detection and appropriate categorization are critical for reducing morbidity and mortality. This study aimed to assess the proportion of HTN-U among HTN-C cases, examine demographic and clinical profiles, evaluate differences in clinical presentation between HTN-U and HTN-E, and identify risk factors for hypertensive crisis. Method: This is an observational cross-sectional study of 164 patients presenting with HTN-C in the Emergency Department of a Tertiary Hospital, using non-probability convenience sampling. Clinical and demographic data were analyzed using descriptive and inferential statistics at the 5% level (p < 0.05). Result: Findings revealed that 103 patients (62.8%) were classified as HTN-U, while 61 patients (37.2%) were classified as HTN-E. The study highlighted a mean age of HTN-C was (mean ± SD = 54.09 ± 15.59), with a male predominance of 99 (60.4%) patients. The most common presentation of HTN Urgency were headache vomiting and epistaxis whereas altered level of consciousness, slurring of speech and blurring of vision was common in hypertensive emergency.. Blurring of vision 5 (81.3%) was common in HTN-E. Risk factors for HTN-C included smoking (p < 0.045), tobacco (p < 0.013), non-compliance with medication (p < 0.034), and ayurvedic medicines (p < 0.016). Conclusion: Hypertensive urgency was more prevalent, and hypertensive emergency cases posed greater risks due to neurological complications. Clinical symptoms of HTN-C provide clues to differentiate hypertensive urgency from hypertensive emergency in the emergency department.